2003
DOI: 10.1097/00006324-200312000-00014
|View full text |Cite
|
Sign up to set email alerts
|

Validity and Reliability of the Revised Convergence Insufficiency Symptom Survey in Children Aged 9 to 18 Years

Abstract: Children with CI showed a significantly higher CISS symptom score than children with normal binocular vision. The results of the study indicate that the CISS is a valid and reliable instrument to use as an outcome measure for children aged 9 to 18 who are enrolled in clinical research concerning CI.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
261
0
1

Year Published

2005
2005
2020
2020

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 257 publications
(272 citation statements)
references
References 20 publications
10
261
0
1
Order By: Relevance
“…Using these diagnostic criteria may overestimate convergence insufficiency. Although the convergenceinsufficiency symptom survey has undergone validation, 274 many of the symptoms in their symptom-scoring system are too vague and repetitive. Two examples are: (1) Do your eyes hurt when reading or doing close work?…”
Section: Complementary Therapy Assessmentmentioning
confidence: 99%
“…Using these diagnostic criteria may overestimate convergence insufficiency. Although the convergenceinsufficiency symptom survey has undergone validation, 274 many of the symptoms in their symptom-scoring system are too vague and repetitive. Two examples are: (1) Do your eyes hurt when reading or doing close work?…”
Section: Complementary Therapy Assessmentmentioning
confidence: 99%
“…A list of common symptoms, which had been agreed by a group of education and health experts with extensive research experience of visual stress, were used to measure the symptoms experienced; a slightly condensed free version of this questionnaire has recently been published online (23). The nature of the questions was similar to those included in other published validated questionnaires (24,25), but they differed in that they provided a shortened, simplified version, which was felt to be more suitable for use with young children. Preintervention and post-intervention the questionnaire was used with participants; they were individually asked if they experienced any of the symptoms when reading (see Table I).…”
Section: Methodsmentioning
confidence: 99%
“…1 The Convergence Insufficiency Symptom Survey (CISS) questionnaire was administered and patient had a high score (Table 1) comparing to a cut off score for her chronological age of less than 16 points. 2 Pupillary reflex test was done using penlight and the pupils were round, equal and reactive to light in each eye. External eye investigation and internal eye examination using slit lamp biomicroscope and direct ophthalmoscope respectively yielded unremarkable results.…”
Section: Case Reportmentioning
confidence: 99%
“…Notwithstanding, the NPC value was still receded and CISS score was clinically still very symptomatic. [2][3][4] An improvement in positive fusional reserve at near now met Sheard's criteria per habitual phoria of 4 prism diopters of exophoria using the break point as used by the CITT study group. 3,4 An improvement with the recovery point in the reserve measurement indicated that her vergence system was developing some stamina to say the least about it.…”
Section: Case Reportmentioning
confidence: 99%